Comparative analysis of the 2022 DfE GCSE Subject Content for French, German and Spanish and its implications for schools. Issue 2 (4th March 2022) - Blow, David; Myers, Helen
ABSTRACT: In the high-stakes accountability English educational system, decisions made by government and agencies about curriculum, pedagogy and assessment drive school planning and actions. This paper analyses the drivers for the recent change to French German and Spanish GCSEs and highlights particular areas of the new specification which may damage the experience of language learners in the secondary school environment. After describing the context for the revisions we question why GCSE subject content has been revised when there is no evidence that a revision would improve uptake or grades. Our detailed comparison of the 2015 and 2022 subject content shows how the emphasis has shifted considerably from the requirement to demonstrate skills needed in realistic, authentic contexts, to demonstrating productive knowledge of a tightly prescribed list of vocabulary, grammar and phonics. We then identify the likely impact on schools of the new subject content. While the ostensible justification of change is to make more accessible and motivating, our view is that it will demotivate and will not reward broader skills which the whole spectrum of ability could demonstrate. We conclude by suggesting the real reason for the changes is part of a concerted government policy to reorientate the teaching of languages.